Subcellular localization of the nodD gene product in Rhizobium leguminosarum. - Schlaman, H R (1989)
In Rhizobium strains the transcription of symbiosis plasmid-localized nod genes, except nodD, is induced by plant flavonoids and requires the nodD gene product. In order to localize NodD protein in R. leguminosarum, a NodD protein-specific antiserum was raised against a lacZ'-'nodD gene fusion product. Using these antibodies, we determined that the NodD protein is located exclusively in the cytoplasmic membrane of wild-type R. leguminosarum biovar viciae cells. This localization is independent of the presence of inducers. In a Rhizobium strain that overproduced the NodD protein, the protein was present both in the cytoplasmic membrane and the cytosol, indicating an influence of the protein abundance on its ultimate subcellular localization. It was estimated that 20 to 80 molecules of NodD protein were present per wild-type Rhizobium cell. A model which combines the localization and the DNA-binding properties of the NodD protein as well as the observed association of flavonoids with the cytoplasmic membrane is discussed.